USING AUTHENTIC VIDEOS FOR YOUNG LEARNERS WHILE TEACHING FOREIGN LANGUAGE (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article discusses how using real videos for young learners in foreign language teaching is a highly effective way to engage students, improve their listening skills and teach them to use real-world languages, and how real videos can be used effectively.